Perancangan Sistem Pencatatan Keuangan Berbasis Microsoft Excel dan Standar Operasional Prosedur (SOP) atas Kas Keluar dan Masuk pada TK Islam Permata Bunda - Fadya Safa Nabilla; Unggul Purwohedi; Gentiga Muhammad Zairin (Jurnal Akuntansi, Perpajakan dan Auditing, 2025)
Financial management in early childhood education institutions requires orderly recording systems and clear operational procedures. Based on the actual conditions at TK Islam Permata Bunda, several problems were identified in the financial recording system, which is still conducted in a simple manner, and the absence of formalized financial Standard Operating Procedures (SOPs) as work guidelines. Financial transactions are not yet recorded in a structured manner, are insufficiently documented, and have not resulted in systematic financial reports. These conditions potentially lead to irregular financial records and make it difficult for the school to conduct effective financial control. This study aims to design a Microsoft Excel–based financial recording system and develop financial SOPs tailored to the needs of TK Islam Permata Bunda. The research employed a development research method using the ADDIE approach, limited to the Analyze, Design, and Development stages. Data were collected through interviews, observations, and documentation. The results indicate that the designed Microsoft Excel–based financial recording system and financial SOPs can assist the school in managing financial records in a more orderly, systematic, and user-friendly manner.